UPAYA PENINGKATAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN IPA MELALUI MODEL COOPERATIVE LEARNING TIPE SNOWBALL THROWING DI KELAS IV SDN 29 SUNGAI LIMAU - Ernita, Ernita (Jurnal Manajemen Pendidikan, 2017)
Achievement or not the purpose of learning is determined by many factors such as teachers in implementing the process of teaching and learning, because teachers can directly influence, foster and improve students' intelligence and skills. To overcome the above problems and to achieve the goal of education maximally, the role of teachers is very important and expected teachers to have a good method of teaching and able to choose the appropriate learning methods and in accordance with the concepts of subjects to be delivered. One of the proper learning model in science learning is Snowball Throwing learning model. Problems to be studied in this research are: Is it through the use of Snowball Throwing learning model to improve the results of science fantasy Class IV SDN 29 Sungai Limau? The purpose of this action research is to improve the learning outcomes of IPA Class IV SDN 29 Sungai Limau through the Snowball Throwing learning model. This study used a classroom action research of two rounds. Each round consists of four stages: planning, execution, observation, reflection. Target of this research is student of Class IV SDN 29 Sungai Limau. The data obtained are quantitative and qualitative data. From the analysis result of IPA learning model has positive impact in improving student learning outcomes marked by the improvement of students' learning mastery in every cycle, that is cycle I 52.63%, and cycle II 94.37%. The conclusion of this research is the Snowball Throwing learning model has a positive influence, that is to improve student learning outcomes which is indicated by the average of students' answers stating that students are interested and interested in the learning model of Snowball Throwing so that they become motivated to learn.